The boy who lived with the bears : and other Iroquois stories - Bruchac, Joseph, 1942- (HarperCollinsPublishers, 1995)
Presents a collection of traditional Iroquois tales in which animals learn about the importance of caring and responsibility and the dangers of selfishness and pride.